A fuzzy MCDM-based approach for renewable energy technologies prioritisation. (2018) - Ebrahimi, Maryam
The main objective of this study is to build a decision model adapted to prioritise renewable energy technologies by applying fuzzy multi-criteria decision-making (MCDM) methods. A comprehensive set of criteria is presented based on sustainability due to its importance in the long-term, particularly in the field of energy which is a key element of sustainable development. They are classified into five categories such as technical, economic, environmental, social, and political criteria. This model is then operationalised in the scope of solar energy technologies in Iran. This paper examines and compares the results of fuzzy TOPSIS and fuzzy PROMETHEE based on a single decision maker. The results show that rather than the two technologies, others in both methods have moderate differences in ranking. However, technological decisions are preferred to be made based on FTOPSIS results because it is considered to be more realistic.